Fezolinetant for treatment of moderate-to-severe vasomotor symptoms associated with menopause (SKYLIGHT 1): a phase 3 randomised controlled study. Issue 10382 (1st April 2023) - Lederman, Samuel; Ottery, Faith D; Cano, Antonio; Santoro, Nanette; Shapiro, Marla; Stute, Petra; Thurston, Rebecca C; English, Marci; Franklin, Catherine; Lee, Misun; Neal-Perry, Genevieve
Summary: Background: Neurokinin 3 receptor antagonists are potential non-hormonal therapies for the treatment of vasomotor symptoms in menopausal women as options are scarce for those who cannot or do not want to take hormone therapy. Fezolinetant is one of the first non-hormonal neurokinin 3 receptor antagonists in development for the treatment of vasomotor symptoms due to menopause. This study investigated the safety and efficacy of fezolinetant for the treatment of moderate-to-severe vasomotor symptoms associated with menopause. Methods: SKYLIGHT 1 is a randomised, double-blind, placebo-controlled, 12-week, phase 3 trial with a 40-week active treatment extension. This trial was done at 97 facilities across the USA, Canada, Czech Republic, Hungary, Poland, Spain, and the UK. Women aged 40–65 years with an average of seven or more moderate-to-severe hot flashes per day were randomly assigned (1:1:1) to once-daily exact-matched placebo, fezolinetant 30 mg, or fezolinetant 45 mg. Randomisation was done using a web-based interactive response system and investigators, project team members, clinical staff, and participants were masked to treatment assignment. Coprimary endpoints were mean change in frequency and severity of vasomotor symptoms from baseline to weeks 4 and 12. The efficacy and safety analyses comprised all randomly assigned participants who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov (NCT04003155 ) and is completed. Findings: Between July 11, 2019, and Aug 11, 2021, 2205 women were recruited of whom 175 were assigned to placebo, 176 to fezolinetant 30 mg, and 176 to fezolinetant 45 mg (175 in the placebo group, 174 in the fezolinetant 30 mg group, and 173 in the fezolinetant 45 mg received at least one dose [safety analysis set]). One participant randomly assigned to fezolinetant 45 mg received fezolinetant 30 mg in error, so the efficacy analysis set (full analysis set) consisted of 173 in the fezolinetant 30 mg group and 174 in the fezolinetant 45 mg group. 23 participants in the placebo group, 31 in the fezolinetant 30 mg group, and 13 in the fezolinetant 45 mg group discontinued treatment before week 12, mostly due to adverse events or participant withdrawal. Compared with placebo, fezolinetant 30 mg and fezolinetant 45 mg significantly reduced the frequency of vasomotor symptoms at week 4 (difference in change in least squares mean –1·87 [SE 0·42; p<0·001], –2·07 [SE 0·42; p<0·001]) and week 12 (–2·39 [SE 0·44; p<0·001], –2·55 [SE 0·43; p<0·001]). Compared with placebo, fezolinetant 30 mg and 45 mg significantly reduced the severity of vasomotor symptoms at week 4 (–0·15 [0·06; p=0·012], –0·19 [0·06; p=0·002]) and week 12 (–0·24 [0·08; p=0·002], –0·20 [0·08; p=0·007]). Improvements in frequency and severity of vasomotor symptoms were observed after 1 week and maintained over 52 weeks. During the first 12 weeks, treatment-emergent adverse events occurred in 65 (37%) of 174 women in the fezolinetant 30 mg group, 75 (43%) of 173 in the fezolinetant 45 mg group, and 78 (45%) of 175 in the placebo group. The incidence of liver enzyme elevations was low (placebo n=1; fezolinetant 30 mg n=2; fezolinetant 45 mg n=0) and these events were generally asymptomatic, transient, and resolved while on treatment or after treatment discontinuation. Interpretation: Data support the clinical use of fezolinetant as a non-hormonal treatment for vasomotor symptoms associated with menopause. The study was placebo-controlled for 12 weeks followed by a 40-week blinded extension to assess the maintenance of effect. Furthermore, the population studied was diverse and representative of the potential target population for fezolinetant therapy. Further characterisation of the benefit of fezolinetant on quality of life, including on symptoms of mood and sexual wellbeing, merits investigation. Funding: Astellas Pharma.